Appointment of forensic examinations during the investigation of violence against a law enforcement officer: problems and ways to solve - V. O. Gusieva (Law and Safety)
The aim of the study was to identify common mistakes made by investigators during the appointment of forensic examinations in criminal proceedings initiated in connection with the commission of violence against law enforcement officers, and possible ways to solve them. To achieve this goal, special research methods were used, namely: the method of system analysis, comparative legal method, system and structural and forecasting method, as well as statistical methods, including methods of grouping and analysis of quantitative indicators. It has been established that forensic examinations play an important role in the investigation of violence against law enforcement officers. It is determined that the subject of forensic examination of living persons (establishing the severity of injuries) is to determine a set of issues regarding the type of injuries, their number, nature and location, age and sequence of infliction, determining their severity etc. It is established that on average during the investigation of crimes of this category two examinations are appointed.